Occurrence, Antimicrobial Resistance, and Virulence Profiles of Salmonella Serovars Isolated from Wild Reptiles in South Africa - Lungile N. Mlangeni; Tsepo Ramatla; Kgaugelo E. Lekota; Cormac Price; Oriel Thekisoe; Che Weldon (International Journal of Microbiology)
Reptiles are carriers of an array of microorganisms, including significant zoonotic bacteria of the genus Salmonella, which cause a disease referred to as salmonellosis that affects both animals and humans. This study investigated the occurrence of Salmonella serovars in wild reptiles at Timbavati Private Game Reserve in Limpopo Province, South Africa, and examined their virulence and antimicrobial resistance gene profiles. A total of 19 wild reptiles were sampled, which resulted in 30 presumptive Salmonella isolates. The isolates were identified using polymerase chain reaction (PCR) by amplifying the invA gene and were further confirmed by 16S rRNA gene sequencing. Salmonella serovars were detected in chameleons (36.8%), lizards (31.6%), snakes (15.8%), and tortoises (15.8%). The use of 16S rRNA gene sequencing revealed that Salmonella enterica subsp. enterica serovar Salamae (30%), S. enterica subsp. enterica (16.7%), S. enterica subsp. enterica serovar Typhimurium (13.3%), and S. enterica subsp. enterica serovar Indiana (13.3%) were the four most common subspecies among the investigated 30 isolates. Detected virulence genes included pagN (100%), hilA (96.7%), ssrB (96.7%), prgH (86.7%), and marT (86.7%). The isolates exhibited resistance to nalidixic acid (43.3%) and kanamycin (43.3%), followed by streptomycin (16.7%) and ciprofloxacin (3.3%). Antibiotic-resistant genes were detected as follows: strA, strB, qnrA, qnrS, parC, aadA, aac(6′)-Ib, and aac(6′)-Ib-cr at 33.3%, 6.7%, 16.7, 13.3%, 10%, 23.3%, 6.7%, and 10%, respectively. The findings highlight the necessity of educational initiatives aimed at reducing reptile-related infections. Effective antibiotic treatment appears promising for infection, given the minimal drug resistance observed in reptile Salmonella serovars in the current study.